2016
DOI: 10.1155/2016/3435791
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, Barriers, and Preferences of European Overweight Women to Adopt a Healthier Lifestyle in Pregnancy to Minimize Risk of Developing Gestational Diabetes Mellitus: An Explorative Study

Abstract: Introduction. We explored beliefs, perceived barriers, and preferences regarding lifestyle changes among overweight European pregnant women to help inform the development of future lifestyle interventions in the prevention of gestational diabetes mellitus. Methods. An explorative mixed methods, two-staged study was conducted to gather information from pregnant European women (BMI ≥ 25 kg/m2). In three European countries 21 interviews were conducted, followed by 71 questionnaires in six other European countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 42 publications
8
48
0
4
Order By: Relevance
“…The findings of period specific determinants are especially relevant when supporting women to adopt a healthy lifestyle continuously in the periods before, during and after pregnancy. The determinants of lifestyle behavior in the pregnancy and postpartum periods are in line with the findings described before [16][17][18][19][20][21][22][23][24]39]. The current research is an important addition to the existing knowledge in identifying preconception period specific determinants.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of period specific determinants are especially relevant when supporting women to adopt a healthy lifestyle continuously in the periods before, during and after pregnancy. The determinants of lifestyle behavior in the pregnancy and postpartum periods are in line with the findings described before [16][17][18][19][20][21][22][23][24]39]. The current research is an important addition to the existing knowledge in identifying preconception period specific determinants.…”
Section: Discussionsupporting
confidence: 83%
“…When considering previous studies on determinants of lifestyle behavior conducted in women of childbearing age, survey studies showed that women wishing to become pregnant were interested in lifestyle programs, especially when tailored to the possibilities within the daily life of women [14,15]. During pregnancy, health of the unborn child was an important motivator for adopting a healthy lifestyle [16][17][18]. On the other hand, pregnant women mentioned that being pregnant is a justification for not worrying about weight and pregnancy is a time to eat for two [16].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…However, they faced barriers that made changes beyond their control. Furthermore, a lack of time especially in multiparous women and being unable to establish communication with nurse assistants for various reasons were mentioned as main barriers (33,36). According to some studies, the training program, the implementation of risk assessment (39,40), customer-centered interventions, short-term motivational interviews, or an increased frequency of being exposed to individuals were facilitators to adopting healthy behaviors (5).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of traditional perspectives in providing healthcare services and men's lack of participation in prenatal care were considered as barriers to the fulfillment of health behaviors (33). Women believed facilitating factors such as having the opportunity to talk to nurse assistants and having various options in terms of time, location and other communication channels (face-to-face interview, telephone and internet) could affect behavioral changes (33,36).…”
Section: Barriers and Facilitators Of Health-promoting Behaviorsmentioning
confidence: 99%
“…While designing the appropriate lifestyle for EWw, the attention should focus on the content itself (a healthy diet, performance of regular physical activity…) but it is also detrimental to facilitate the adherence to this change. A main goal should be to consider counseling as a key aspect, where these women should be educated about GDM risks, as well as discussing individual impediments they might encounter to fulfill the lifestyle changes 28. In addition, providing all pregnant women with the same interventional tools used for GDM treatment, regardless of their GDM condition or PPBMI, should be envisioned as a possible universal clinical practice.…”
Section: Discussionmentioning
confidence: 99%